Mineralogical and geochemical characteristics of particle PM10 in Tikveš area and their infuence in the environment - Boev, Ivan; Stafilov, Trajce (Society of Chemists and Technologists of Macedonia, 2016)
In this work the results of investigation of the geochemical and mineralogical characteristics of particulate matters below 10 μm (PM10) collected from Tikveš area, Republic of Macedonia, are presented. For that purpose, PM10 samples were collected from the city of Kavadarci and from the area close to the ferronickel smelter plant. As well as the concentration of PM10, the chemical content and mineral phases of dust samples and their relations to some anthropogenic sources are investigated. Determination of the content of various elements was performed by using inductively coupled plasma–mass spectrometry (ICP-MS). Scanning electron microscopy–energy dispersive spectroscopy (SEM-EDS) was used for the determination of mineralogical phase content. From the obtained results, it can be concluded that the concentration of PM10 in the vicinity of the ferronickel smelter is much higher than those from the city of Kavadarci. It was found that PM10 samples collected close to the ferronickel smelter plant have a higher content of some elements present in higher concentrations in the ore processed in the ferronickel smelter plant (Fe, Ni, Cu, Zn, Ag, Cr) than those from the town of Kavadarci, showing their anthropogenic origin. The investigations performed by applying electron microscopy (SEM-EDS) unequivocally confirmed the results obtained using X-ray diffraction and ICP-MS. Namely, mineral phases present in the particulates were found to be those which are present in the ore used in the process in the metallurgical plant, including chlorite, amphibole, pyroxene, magnetite, chromites, quartz, calcite or plagioklas clay minerals.